Modified FCS-MPC algorithm for five-leg voltage source inverter - Riyadh Ghanem Omar (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper represents a test of a modified algorithm to minimize the cost function in the traditional finite control-set model predictive current control (FCS-MPC) to control the (five-leg) DC voltage input inverter. A Matlab/Simulink description of a system presents a certain deviation limits between the reference and the actual measured phase currents, also the model implements a load current limitation. The algorithm picks out a proper switching state, which makes the lower error value between the wanted and the prognosticated currents; the proposed technique sets the chosen switching state as a driving signal to the ten switches. The modified program eliminates the switching combination with error values above the requested ones. Thereafter the system response enhanced by lowering the overshoots. The rigidness of the model is examined by using a step change in reference signals.